Implementasi Pendidikan Agama Islam Dalam Pembinaan Moral Remaja (Studi Kasus di Pesantren Modern Muadalah dan Pesantren Salaf/ Tradisional) - Taufik Rizki Sista; Safiruddin Al-Baqi (At-Ta'dib, 2018)
The Islamic education cannot be separated from moral guidance or moral education. Islamic boarding school institutions are the origin of Islamic education institution in Indonesia, the pesantren institution is famous for its moral guidance for students. In the present day, there are two types of pesantren institutions, the traditional pesantren and modern pesantren, which both of them has its own characteristics in practice of moral development for its students.This research is a qualitative research with a case study model. The object of this research is Pondok Modern Darussalam Gontor campus 2 and Pondok Pesantren Darul Huda Mayak Ponorogo.The purpose of this study was to (1) find out how the Islamic Education model in Pondok Modern Darussalam Gontor and Darul Huda Mayak Islamic Boarding School. (2) To find out how the moral development process in each pesantren institution.The results of this study are (1) the model of religious education carried out at Pondok Modern Darussalam campus 2 refers to the curriculum of Kulliyatul Muallimin Al-Islamiyah where the coverage of knowledgeis 100% religion and 100% scientific knowledge, while the implementation of religious education in the Darul Huda Mayak Islamic boarding school refers to the principle of Salafiyah Hadistah, which is the education with traditional salaf curriculum and contemporary education methods. (2) The implementation of moral guidance activities at Pondok Moden Darussalam Gontor Campus 2 is to optimize the 24-hour education process based on daily discipline and the pesantren curriculum, while the implementation of moral guidance in the Darul Huda Mayak Islamic Boarding School is carried out with (1) internalization of the value of the Kitab Kuning in daily life and (2) habituation of religious activities in pesantren.